كۆنسێپتی كۆكردنهوەی ماتریاڵ له نێو هونهری پهیكهرسازی هاوچهرخ له ههرێمی كوردستاندا (بهشێك له كورتكراوەی توێژینهوەی ماستهر) - عزیز, سهربهست محسین; تاهر, ئازاد جهمال (Sulaimani Journal for Humanities, 2021)
This research has the title (The Concept of materials collecting in Contemporary Sculpture in the Kurdistan Region) It consists of three sections, the first section includes (the problem of research, the importance of research, the purpose of the research that displays the concept of materials collecting in contemporary sculpture in the Kurdistan Region) The research period between the years (2001-2019), concept and terms. The second section includes (the form of research theory), which in turn consists of three researches, the first research: includes The concept of collecting.The concept of collecting in ancient civilizations: The concept of collecting in the civilization of ancient Greece:.The concept of collecting in the ancient civilization of Egypt:.The concept of collecting in the ancient civilization of Iraq.The concept of collecting in the civilization of Rome:.The concept of collecting in the different civilizations. The second research: includes The concept of the material: - the material in the era of ancient Egypt: section, 3- The material in the industrial age:.The material in the modern era.: The third research: includes The material and Art of Sculpture:.- The material in the era of modern sculpture : The material in the era of contemporary sculpture - - The collected contemporary sculpture in Iraqh.- The collected sculpture in the Kurdistan . The third section: How to do the research, which consists of (research pattrens, means of information collecting, research and study method). The researcher adopted in his research (the descriptive study) and after studying the patterns, the results were as follow: Using more than one material in the artistic form, which in turn gave a new shift to contemporary sculptures in the Kurdistan Region as it is presented in all works. Using ready materials by all Kurdistan artists as they appear in all works